2006
DOI: 10.1101/gad.1383206
|View full text |Cite
|
Sign up to set email alerts
|

Selective and antagonistic functions of SWI/SNF and Mi-2β nucleosome remodeling complexes during an inflammatory response

Abstract: Studies of mammalian genes activated in response to an acute stimulus have suggested diverse mechanisms through which chromatin structure and nucleosome remodeling events contribute to inducible gene transcription. However, because of this diversity, the logical organization of the genome with respect to nucleosome remodeling and gene induction has remained obscure. Numerous proinflammatory genes are rapidly induced in macrophages in response to microbial infection. Here, we show that in lipopolysaccharide-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
418
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(459 citation statements)
references
References 59 publications
35
418
1
1
Order By: Relevance
“…1) (Weinmann et al 1999;Ramirez-Carrozzi et al 2006). Similar results were later obtained with the Il12b enhancer ( Fig.…”
Section: Nucleosome Remodeling At Il12bsupporting
confidence: 76%
“…1) (Weinmann et al 1999;Ramirez-Carrozzi et al 2006). Similar results were later obtained with the Il12b enhancer ( Fig.…”
Section: Nucleosome Remodeling At Il12bsupporting
confidence: 76%
“…TLR activation of these genes requires the active removal of SMRT, in addition to the recruitment of activators and coactivators. ABIN-2 has also been shown to interact with Baf60a, a subunit of the SWI/SNF chromatin-remodeling complex [64], which positively regulates a subset of TLR4-induced genes in macrophages [65]. Tandem-affinity purification has demonstrated that ABIN-2 complexes with Rel subunits [56], although it is not known whether these are direct interactions or are mediated via NF-κB1 p105.…”
Section: Regulation Of Tpl-2 Stability By Abin-2mentioning
confidence: 99%
“…4B), indicating that its expression requires de novo protein synthesis. These data place tenascin-C in the group of secondary inflammatory response genes (that includes IL-6 and IL-12), which require new protein synthesis for both transcription and nucleosome remodeling (33).…”
Section: Tenascin-c Expression Is Transcriptionally Regulated During mentioning
confidence: 99%